Darna and the intermediality of the Filipino superhero genre - Brillon, Cherish Aileen A.; Capili, Jose Wendell; Brillon, Cherish Aileen A. (Quezon City University of the Philippines, 2018)
Superheroes are big business in today's globalized world. They fill the movie houses, bestow celebrity status, and create spin-offs in a variety of platforms. At a time when culture has become a dynamic force in the negotiation between politics, culture, and economy, and with superhero narratives becoming the currency in today's popular culture, it is time to revisit our superheroes and locate them within contemporary global discourses. Related literature revealed the lack of studies that problematize the constitution, elements, conventions, and practices of our superhero genre because of our tendency to subsume it under other categories. This led me to explore the constitution of our local superhero genre using Mars Ravelo's Darna as a template for analysis. Darna's intermediality-- her popularity, appeal, and success across platforms made her the perfect vehicle to jumpstart my inquiry into the subject.This dissertation utilizes an interpretivist approach and borrows from the notion of intermediality (Jensen, 2016; Kukkonen, 2013; Rajewski, 2005). It aims to address the following objectives: to propose an alternative way of historicizing the Filipino superhero genre through the lens of auteurship; to describe the generic elements and iconographies that constitute the Filipino superhero genre; to locate the role of adaptation and nostalgia in interpreting Darna's intermediality; and to explain the role of Darna in creating a discourse on superhero body and power.This dissertation attempts to carve a space for the discussion and importance of Filipino superheroes who have existed for as long as and amidst the overwhelming narratives of Western superheroes. It hopes to expand the discussion on how popular culture figures, specifically superhero characters, can transcend their juvenile and commodified reputation into a serious field of inquiry for scholars and academics.
Includes bibliographic references (pages 298-319).
Thesis
Keywords: Literature -- Philippines